MAKING BRIQUETTES FROM WASTE OF COCONUT SHELL AND PEANUT SHELL - Yusraida Khairani Dalimunthe; Sugiatmo Kasmungin; Eddy Sugiarto; Lisa Sugiarti; Alyssa Lagrama (Universitas Trisakti, 2021)
Aims: This study aimed to increase the utilization of biomass-derived from the waste of coconut and peanut shells by making them as briquettes, as an alternative to fuel. The scarcity of petroleum because of its increasingly limited existence encourages all parties to take part in the development and discovery of new alternative energies. This is expected to overcome one of the most important of the many problems facing this country. The method used in this research is to start with a literature study of materials from various sources about the benefits and manufacturing of briquettes from biomass waste as an alternative energy source to be further tested for quality. This involves a heat test, water content test, ash content test and determination of the flying matter. Results: The test results showed that natural gas emissions were below threshold, namely 0-30 ppm CO, 0-3.6 ppm H2S, and undetectable NOx. After evaluation, the results showed that with the addition of 30% of the biomass, the ignition time was reduced and the remaining unburned briquettes or bottom ash was reduced by 68.68%. Conclusion, significance, and impact of study: The results help the community and the parties involved related to appropriate bio briquettes technology. It also eventually becomes one of the solutions to assist the government in solving problems related to alternative fuels to petroleum.